2019
DOI: 10.31557/apjcp.2019.20.11.3407
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis between the Gail, Tyrer-Cuzick and BRCAPRO Models for Breast Cancer Screening in Brazilian Population

Abstract: Objective: To analyze the diagnostic accuracy of predictive models of breast cancer risk for the Brazilian population. Method: A cross-sectional, study was conducted in a sample of 382 women aged 35-69 years who were users of the Unified Health System (SUS) residing in a municipality in southern Brazil. Results: The results showed that the Tyrer-Cuzick model had the highest mean risk values and estimates (proportion) for predicting the 5-year risk of breast cancer, reaching a maximum risk of ±1.63% in the 60-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…This web-based DA incorporates 2 complementary theoretical frameworks-shared decision making [23] and self-determination theory (SDT) [24]-to engage women in planning a preference-sensitive course of decision making about chemoprevention. SDT has at its core the concept of autonomous motivation [24][25][26] and describes autonomous choices as those that a person could fully endorse upon reflection [27][28][29]. This is contrasted with behaviors or choices that feel controlled or coerced by another person.…”
Section: Interventionmentioning
confidence: 99%
“…This web-based DA incorporates 2 complementary theoretical frameworks-shared decision making [23] and self-determination theory (SDT) [24]-to engage women in planning a preference-sensitive course of decision making about chemoprevention. SDT has at its core the concept of autonomous motivation [24][25][26] and describes autonomous choices as those that a person could fully endorse upon reflection [27][28][29]. This is contrasted with behaviors or choices that feel controlled or coerced by another person.…”
Section: Interventionmentioning
confidence: 99%
“…However, it can be difficult to use and requires a provider to enter data, thus limiting its use outside of the clinic (24,25). Conflicting data exist in the literature regarding the level of accuracy between these two models, with some studies indicating that the TC model is superior in terms of specificity, sensitivity, and positive and negative predictive value (32,33), while others reporting greater AUC and specificity for the Gail model (34,35). Guidelines warn against the use of the Gail model when assessing MRI eligibility for screening purposes due to accounting for limited family history (31).…”
Section: Discussionmentioning
confidence: 99%
“… 29 A cross-sectional study, using three breast cancer risk assessment tools (Gail, Tyrer-Cuzick, and BRCAPRO) and including 382 women 35-69 years of age in the South region of Brazil, has demonstrated that the tools can identify up to 8.8% of women 35-39 years as having high risk for breast cancer. 30 These tools can also identify individuals at risk for Hereditary Breast and Ovary Cancer (HBOC) syndrome. One study has demonstrated the prevalence of BRCA1 or BRCA2 mutation in 21.5% of 349 unrelated individuals in Brazil with personal or familial high risk for HBOC syndrome.…”
Section: Discussionmentioning
confidence: 99%